PENERAPAN KETELADANAN GURU DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER PADA PEMBELAJARAN AQIDAH AKHLAK DI MTS MIFTAHUL ULUM KANTAN - Bandi Bandi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
This research originated from looking at the phenomenon that occurred at MTs Miftahul Ulum Kantan where some students were lacking in instilling the values ​​of character education so that they did not match the expectations of the teacher, therefore the aqidah moral teacher tried to instill the values ​​of character education. This study aims to obtain clear information about: 1) Implementation of teacher exemplary implementation in instilling character education values ​​in learning aqidah morals at MTs Miftahul Ulum Kantan. 2) Evaluation of the implementation of exemplary teacher in instilling character education values ​​in learning aqidah akhlak at MTs Miftahul Ulum Kantan. 3) Supporting and inhibiting factors for implementing teacher exemplary in instilling character education values ​​in learning aqidah akhlak?. The subjects of this study were teachers of aqidah akhlak, school principals, students of MTs Miftahul Ulum Kantan. To obtain data related to the focus of the study, researchers conducted interviews, observation and documentation. The data analysis technique used is qualitative data analysis. In this study, researchers used two techniques, namely: 1) Triangulation Technique, 2) Member Check Technique. The results of the study can be concluded: 1) The implementation of teacher exemplary application in instilling character education values ​​in learning aqidah akhlak at MTs Miftahul Ulum Kantan: guiding, assessing, collaborating, motivating. 2) Evaluating the implementation of teacher exemplary practices in instilling character education values ​​in learning aqidah akhlak: providing guidance to students, collaborating between teachers and parents, motivating students by providing stories that arouse students' enthusiasm, holding extracurricular activities, conducting evaluation of activities that have been carried out. 3) Supporting factors and obstacles to the implementation of teacher exemplary practices in instilling character education values ​​in learning aqidah akhlak at MTs Miftahul Ulum Kantan: a) Supporting factors; providing guidance for fardhu prayer, giving role models, physical or spiritual condition of healthy students, family condition care for students' Islamic religious education, cooperation between teachers, principals and parents of students. b) Inhibiting factor; students are not enthusiastic about following the guidance from the teacher, facilities and infrastructure are still minimal, there are some parents who do not cooperate in building student morals, low parental Islamic education, lack of support from students' parents.